Early Detection of Dental Caries Prevention in Children by Toothbrushing at SD Kampung Parung Ponteng, Tajur Village, Bogor Regency - Wahyu Budi Setiawati; Sapta Prayoga; Vinny Maulidia (PT FORMOSA CENDEKIA GLOBAL, 2022)
Dental caries is a problem that is often found in poor dental health, and this is often experienced by children aged 4-6 years because children have not been able to brush their teeth properly, poor diet. The results of the characteristics of the health survey, the prevalence of dental caries in children aged 3-5 years by 81.7%. The prevalence of dental caries according to age three years (60%), age four years (85%), and age six years (86.4%) thus the age of toddlers is a group prone to occur dental caries. The age of the child to maintain dental health is indeed not easy to be able to independently care for his teeth, let alone brush his teeth twice a day, at an early age, children do not understand the importance of dental health. Dental health needs to be applied from an early age so that their teeth grow well.